Chemical Profiling and Dose-Dependent Assessment of Fear Reducing and Memory-Enhancing Effects of Solanum virginianum in Rats. Issue 1 (3rd March 2021) - Javaid, Usman; Javaid, Sana; Ashraf, Waseem; Rasool, Muhammad Fawad; Noman, Omar M.; Alqahtani, Ali S.; Majeed, Abdul; Shakeel, Waleed; Albekairi, Thamer H.; Alqahtani, Faleh; Imran, Imran
The current study was planned to investigate the pharmacological basis of Solanum virginianum extract (SV.CR) pertaining to anxiolytic, antidepressant and memory-enhancing effects in rats. The SV.CR was analyzed in-vitro for phytoconstituents, antioxidant potential and anticholinesterase activity. The rats treated in a dose-dependent manner (25, 50 and 100 mg/kg of SV.CR) were subjected to behavioral tests for anxiety, depression and memory judgment followed by biochemical studies. A notable dose-dependent anxiolytic potential of SV.CR was observed in elevated plus maze and open field tests (P < 0.05). The decreased immobility time of the treated rats in the forced swim test (P < 0.01) unveiled the plant's potential to reduce depression. Moreover, SV.CR treatment also reversed scopolamine-impaired cognition (P < 0.05) in various deployed memory and learning tasks. Biochemical studies of brain homogenates of SV.CR treated animals demonstrated decreased anticholinesterase activity and lipid peroxidation levels whereas increased levels of superoxide dismutase and glutathione peroxidase (P < 0.05 vs scopolamine group) were noted. The scientific validation of the study supported the use of Solanum virginianum in reducing anxiety, depression and amnesia in experimental models. Phytoconstituents in SV.CR such as oleanolic acid and caffeic acid might have played a significant neuroprotective role via modulation of oxidative stress and neurochemical aspects.